PERSPECTIVE—The Sociological Ambivalence of Bureaucracy: From Weber via Gouldner to Marx - Adler, Paul S. (Organization Science, 2012)
Reports of the demise of the bureaucratic form of organization are greatly exaggerated, and debates about bureaucracy's functions and effects therefore persist. For many years, a broad current of organizational scholarship has taken inspiration from Max Weber's image of bureaucracy as an “iron cage” and has seen bureaucracy as profoundly ambivalent—imposing alienation as the price of efficiency. Following a path originally sketched by Alvin Gouldner [Gouldner, A. W. 1954. Patterns of Industrial Bureaucracy. Free Press, Glencoe, IL], some recent research has challenged this view as overly pessimistic, arguing that bureaucracy need not always be coercive but can sometimes take a form that is experienced as enabling. The present article challenges both Weber's and Gouldner's accounts, arguing that although bureaucracy's enabling role may sometimes be salient to employees, even when it is, bureaucracy typically appears to them as ambivalent—simultaneously enabling and coercive. I offer an unconventional reading of Marx as a way to make sense of this ambivalence.